Disease Modification in Multiple Sclerosis by Flupirtine—Results of a Randomized Placebo Controlled Phase II Trial - Dörr, Jan; Wernecke, Klaus-Dieter; Würfel, Jens; Bellmann-Strobl, Judith; Siffrin, Volker; Sättler, Muriel B.; Simons, Mikael; Linsa, Andreas; Tumani, Hayrettin; Paul, Friedemann (Frontiers in Neurology, 2018)
Central nervous system inflammation and neurodegeneration are the pathophysiological hallmarks of multiple sclerosis (MS). While inflammation can readily be targeted by current disease modifying drugs, neurodegeneration is by far less accessible to treatment. Based on suggested additional neuroprotective capacities of the orally available non-opioid and centrally acting analgesic drug flupirtine maleate we hypothesized that treatment with flupirtine maleate might be beneficial in MS patients. The flupirtine as oral treatment in multiple sclerosis (FLORIMS) study was a multi-center, randomized and stratified, placebo-controlled double-blind phase II trial to investigate safety and efficacy in terms of clinical and radiographical activity of flupirtine maleate (300 mg per day) given orally for 12 months, add-on to interferon beta 1b subcutaneously in patients with relapsing remitting MS. Due to a substantial delay in recruitment, enrolment of patients was prematurely terminated after randomization of only 30 of the originally planned 80 patients. Of these, 24 regularly terminated study after 12 months of treatment. Data were analyzed as originally planned. Treatment with flupirtine maleate was overall well tolerated. We observed moderate and asymptomatic elevations of liver enzymes in several cases but no overt hepatotoxicity. Neither the intention to treat nor the per protocol analysis revealed any significant treatment effects of flupirtine maleate with respect to occurrence of MS relapses, disability progression, or development of new lesions on cranial MRI. However, substantial methodological limitations need to be considered when interpreting these results.